2020
DOI: 10.1590/0037-8682-0356-2019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Inflammatory Markers between Adult and Pediatric Brucellosis Patients

Abstract: Introduction: This study aimed to evaluate and compare with healthy control subjects the levels of indirect inflammatory markers such as mean platelet volume (MPV), platelet to lymphocyte ratio (PLR), and neutrophil to lymphocyte ratio (NLR) in adults and children with brucellosis. Methods: White blood cell, neutrophil, lymphocyte, and platelet counts, and C-reactive protein (CRP) levels were retrospectively recorded for all participants. Results: NLR and neutrophil counts were significantly higher in adult pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
(27 reference statements)
3
4
0
Order By: Relevance
“…A study by Patel et al [24] was similar to our results, and it was signi cantly higher in RDW and signi cantly lower in NLR levels of brucella epididymo-orchitis when compared to non-brucella epididymo-orchitis. The study by Tekin et al [22] and the study by Küçükbayrak et al [16] was similar to ours as well. However, Togan et al [15] reported RDW level was not signi cantly higher in the acute brucellosis patients compared to that of the controls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A study by Patel et al [24] was similar to our results, and it was signi cantly higher in RDW and signi cantly lower in NLR levels of brucella epididymo-orchitis when compared to non-brucella epididymo-orchitis. The study by Tekin et al [22] and the study by Küçükbayrak et al [16] was similar to ours as well. However, Togan et al [15] reported RDW level was not signi cantly higher in the acute brucellosis patients compared to that of the controls.…”
Section: Discussionsupporting
confidence: 91%
“…Although there are a few studies about the hematologic effects of the brucellosis in literature [15,22,23], not precisely clear pathogenesis of alteration in RDW, which may be associated with morbidity in this disease, is still lacking. Our ndings showed that RDW levels were signi cantly higher in brucellosis group when compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Adults with CSU had higher NLR and PLR than children with CSU. Our findings regarding increased NLR in adults are similar to those in patients with atopic dermatitis and brucellosis ( 15 ). However, this study did not find any significant difference in PLR between children and adults.…”
Section: Discussionsupporting
confidence: 86%
“…A previous study showed that adult patients with brucellosis had a significantly higher Neutrophil to Lymphocyte ratio (NLR) compared to children. Existing literature also highlights that higher NLR values are observed in inflammatory processes compared to the non-inflammatory ones, therefore NLR may be used in the diagnosis and follow-up of brucellosis cases [16]. An additional study also suggested that increased serum levels of hepcidin (compared to the CRP levels) in patients with brucellosis can be used as a diagnostic biomarker of inflammation and active disease [17].…”
Section: Discussionmentioning
confidence: 99%